The Palestinian Administrative Court’s Oversight of Abuse of Power in the Context of Digital Transformations - Kalaylih, Ihab; Hamid, Fouad (Journal of Palestine Ahliya University for Research and Studies, 2025)
This study aims to analyze the extent to which the Palestinian Administrative Court can exercise control over the abuse of power in the context of digital transformations. The study adopted a descriptive-analytical approach, and the results showed that abuse of power is one of the most serious defects in administrative decisions, as it is linked to the purpose of the decision and the intent of the administration, rendering the decision illegitimate if it is used to achieve unlawful or personal objectives. Digital transformations have also introduced new forms of abuse, notably algorithmic bias, data-driven bias, lack of transparency, and the unauthorized delegation of authority to intelligent systems, which are difficult to control using the traditional tools of the administrative court. The study indicated that conventional judicial tools are no longer sufficient to regulate digital abuse, and the absence of legislation governing digital decisions increases the likelihood of abuse without accountability. Accordingly, the study recommends developing the Palestinian legislative framework to define digital administrative decisions and their validity conditions, establishing rules for transparency and accountability, creating specialized technical units within the judiciary to provide technical expertise to judges, expanding the administrative judge’s authority to request technical documents related to digital decisions and annul the decision if the administration refuses to provide them, and enhancing continuous training for administrative judges in artificial intelligence and digital administration to ensure effective oversight. The scientific originality of this study lies in linking judicial oversight of abuse of power to digital transformations and the introduction of artificial intelligence into the Palestinian administration, providing practical, legal, and technical solutions to develop the role of the Administrative Court in the digital environment, a topic that has not been deeply explored in previous Palestinian studies.